INCREASING THE CAPACITY OF VILLAGE APPARATUS IN IMPLEMENTING PUBLIC SERVICE FUNCTIONS IN BACIRO VILLAGE, GONDOKUSUMAN SUB-DISTRICT, YOGYAKARTA CITY - Rahmadanita, Annisa; Wue, Bernadetha Clara Josephine (Institut Pemerintahan Dalam Negeri, 2024)
Efficient and effective public services are important to fulfill the needs of the community. Increasing the capacity of village apparatus in implementing public service functions is the key. However, village apparatus participation in increasing knowledge and skills related to tasks and functions in Baciro Village is low. This study aims to analyze and describe the capacity building of the village apparatus in implementing public service functions in Baciro Village, Gondokusuman, Yogyakarta City. This study used a quasi-qualitative method. Data collection techniques covered interviews, observation, and documentation. The results of the study showed that capacity building covered three dimensions, namely human resource development, organizational strengthening, and institutional reform. Meanwhile, human resource development needs to be improved in terms of quality and quantity so the village apparatus can be competent in helping the community in solving obstacles. In terms of organizational strengthening, the existing organizational structure is clear and the village apparatus understands their duties and responsibilities. In terms of institutional reform, the services provided are always transparent so that the community can easily access information and supervise all aspects carried out by the village apparatus for the welfare of the community and the interests of the organization. In this case, the apparatus has to be professional in carrying out their duties. It can be concluded that the capacity building of the apparatus in organizing public service functions in Baciro Village is considered in a fairly good category but it requires improvement in some aspects.